Pola Pewarisan Adaptasi Kedelai (Glycine max L. Merrill) terhadap Cekaman Naungan Berdasarkan Karakter Morfo-Fisiologi Daun - , Kisman; , Trikoesoemaningtyas; , Sobir; Nurul Khumaida; Didy Sopandie (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2008)
The objective of this study was to analyze the inheritance pattern of soybean adaptation to shade stress based on leaf morpho-physiological characters. Genetic materials used in this study consisted of 22 plants of low irradiance (LI)-tolerant genotype (Ceneng) and 22 plants of LI-sensitive genotype (Godek); 21 plants of F1 (Ceneng x Godek); and 114 plants of F2 populations (derived from F1). These populations were planted under shading of paranet 50%. The population was arranged in a Randomized Complete Block Design with two replicates. Analysis of inheritance of soybean adaptation involved estimation of heritability (broad sense) and gene action. Results of this study showed that: adaptation of soybean to low light stress based on characters of yield per plant was highly heritable (68% of broad sense) with partial dominant mode of action. Characters of leaf area and specific leaf weight were highly (68% of broad sense) and moderately (48% of broad sense) heritable, respectively, with additive mode of action. Soybean adaptation based on leaf physiological characters (chlorophyll contents) was highly heritable (70% - 86% of broad sense) in epistatic mode of action.   Key words:  Soybean, leaf morpho-physiological character, heritability, gene action